ANALISIS HAMBATAN KOMUNIKASI PADA KOMUNIKASI INTERNAL ORGANISASI KARANG TARUNA KELURAHAN BAMBU APUS SELAMA PANDEMI COVID-19 - Guritno Priyo Utomo (2021)
Karang Taruna is an organization that focuses on social and youth fields, especially in community social empowerment. Based on initial observations made in the Cipayung District, East Jakarta City, there are three Karang Taruna organizations at the sub-district level that are still active. The Youth Organizations are the Youth Organizations of Bambu Apus Village, the Youth Organizations of Lubang Buaya Village, and the Youth Organizations of Cilangkap Village. Karang Taruna of Bambu Apus Village is the organization that has the most problems in its environment than the other two Karang Taruna organizations. This is because the Karang Taruna of Bambu Apus Village has not been able to carry out any activities since the change of new management and also since the Covid-19 pandemic. In addition, these problems also indicate if there are communication problems, where they are not able to minimize psychological barriers in their organization. This research uses a qualitative approach with a case study method, where the selected research objects are three organizational administrators as key informants, two organizational members, and one coordinator as an informant. The research was carried out using observation and in-depth interviews with data validity techniques using source triangulation. The results of the study were obtained if there were psychological barriers caused by the chairman, public relations, members, and problems with the coordinator. In addition, additional information was obtained regarding the success of the work program and the communication process.